THE STAGE CHANGES OF ROCKS AND MINERALOGY OF MERCURY ORES IN DONETSK BASIN - KURYLO, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
It is stated interconnection between the mineral composition of deposits and ore manifestations mercury in Donetsc basin and postdiagenetic changes of rocks.